THE APPROPRIATION OF CHARACTERS IN ONLINE FAN FICTION OF RUNNING MAN TELEVISION SHOW - Aini, Rahma (2015)
This research paper examines the appropriation of characters in online fan fictions of Running Man Television Show. The aim of this research is to analyze the appropriation of characters in online fan fiction of Running Manthe TV Show by the construction of its members: life background of the members, the identification of members, and the characterizations of the members. The researcher collects the data by analyzing two online fan fictions of Running Man which are written by American. The research is drawn upon the appropriation approach proposed by James O. Young (2008) and the characters are analyzed through Rimmon - Keenan approach of characterization (2005). The results show that the members of Running Man are appropriated to online fan fiction by means of appropriating the life background of the members, appropriating the identification of the members in the TV Show, and appropriating the characterization of the members. In addition, the appropriations produce gender stereotype and assimilation argument. Key Word: Appropriation, Fan Fiction, Character Penelitian ini meneliti apropriasi karakter dalam fiksi penggemar Running Man. Tujuan penelitian ini adalah untuk menganalisa appropriasi karakter dari fiksi penggemar Running Man melalui konstruksi karakter dari setiap anggota Running Man. Peneliti mengumpulkan data dengan menganalisa dua fiksi penggemar dari Running Man yang ditulis oleh orang Amerika. Penelitian ini menggunakan pendekatan apropriasi yang dikemukakan oleh James O. Young (2008) dan anggota Running Man/karakter diteliti dengan pendekatan Rimmon - Keenan (2005) tentang karakterisasi. Hasil penelitian menunjukkan bahwa anggota Running Man diapropriasi kedalam fiksi penggemar melalui apropriasi latar belakang, identifikasi di TV Show, dan karakterisasi dari anggota Running Man. Selain itu, apropriasi menghasilkan gender stereotip dan asimilasi argumen. Kata Kunci: Apropriasi, Fiksi Penggemar, Karakter